THE ROLE OF HALAL LABELING AS MODERATING BRAND IMAGE, PRODUCT QUALITY, AND PRICE ON THE PURCHASE INTENTION OF COSMETIC PRODUCTS - Fachrozi, Fachrozi; Mariana, Mariana; Riadi, Selamat (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This study aims to examine and analyze the role of the halal label in moderating the effect of brand image, product quality, and price on cosmetic purchase intention. The method used is quantitative. The data used is a questionnaire. The data analysis technique uses Partial Least Square (PLS). The results showed that brand image and product quality significantly impact purchasing interest with p-values of 0.000<0.05 and 0.020<0.05, respectively. On the other hand, the Price and Halal Labels have no significant effect on purchasing intention, as evidenced by their respective p-values of 0.232 and 0.562>0.05. As a moderating variable, the Halal Label can only moderate the effect of Price on Purchase Intention with a significance p-value of 0.019 < 0.05. However, the Halal Label cannot moderate the influence of Brand Image and Product Quality variables on cosmetic Purchase Intention.